2016
DOI: 10.4238/gmr.15016958
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters for stayability and their associations with traits of economic interest in Gir dairy cows

Abstract: ABSTRACT. The objective of the present study was to estimate genetic parameters for stayability at 60 months of age (STAY60) and its association with first lactation cumulative milk yield (P305), age at first calving (AFC), and first calving interval (FCI), in order to adopt these traits as selection criteria for longevity in Gir dairy cattle. Records for 2770 cows born between 1982 and 2008 from six herds in the Brazilian states of Minas Gerais, São Paulo, and Paraíba were analyzed. The (co)variance component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Grossi et al (2009); Buzanskas et al (2010) and Bernardes et al (2015) estimated lower AFC heritability for Nellore, Canchim and Tabapuã cattle, respectively. Moreira et al (2015) and Silva et al (2016) reported higher AFC heritability estimates, 0·2 ± 0·01 and 0·3 ± 0·06 for Nellore and Gir, respectively. These findings would predict that direct selection for AFC might result in slow improvement compared to selection for other reproductive traits such as HP.…”
Section: Discussionmentioning
confidence: 91%
“…Grossi et al (2009); Buzanskas et al (2010) and Bernardes et al (2015) estimated lower AFC heritability for Nellore, Canchim and Tabapuã cattle, respectively. Moreira et al (2015) and Silva et al (2016) reported higher AFC heritability estimates, 0·2 ± 0·01 and 0·3 ± 0·06 for Nellore and Gir, respectively. These findings would predict that direct selection for AFC might result in slow improvement compared to selection for other reproductive traits such as HP.…”
Section: Discussionmentioning
confidence: 91%
“…There is a lack of studies reporting the genetic correlation between MY305 and LG in buffaloes, but some studies have reported genetic correlation estimates for these traits in dairy cattle (0.04 to 0.35; Wasana et al, 2015). Silva et al (2016) estimated a positive genetic correlation (0.61) between the permanence in the herd at 60 months and MY305 in a herd of dairy Gyr cattle, concluding that selection for MY305 could be used to improve the animals' ability to remain in the herd. Stefani et al (2018) found a negative genetic correlation (−0.25) between permanence in the herd at 60 months of age and MY305 in Holstein cattle.…”
Section: My305mentioning
confidence: 99%